Physical properties of nanosystems - Bonca, Janez (NATO Science for Peace and Security Series B: Physics and Biophysics, 2011)
Recent advances in nanoscience have demonstrated that fundamentally new physical phenomena are found when systems are reduced to sizes comparable to the fundamental microscopic length scales of the material investigated. There has been great interest in this research due, in particular, to its role in the development of spintronics, molecular electronics and quantum information processing. The contributions to this volume describe new advances in many of these fundamental and fascinating areas of nanophysics, including carbon nanotubes, graphene, magnetic nanostructures, transport through coupled quantum dots, spintronics, molecular electronics, and quantum information processing.